Economic policy in Australia : the case for reform - McFarlane, Bruce (Melbourne, Australia : F. W. Cheshire Publishing Ltd., 1968)
In Australian discussion on economic reform, there is a tendency to blame economic stagnation not on self-interest groups and political pressures but on ideologies and outmoded economic theories. Many examples of the impact of vested interests are given in Chapters 3 and 4. The activities of interest groups gave rise to a particular political style in Australia after 1949; this process is outlined in Chapters 5-10. Also Chapters 10-13, the question is raised as to why there should be only 'reform from above' rather than 'do-it-yourself reform'.
Includes bibliographical references and index.
ne 11/06/2018
Loans
Keywords: Economic Policy; Australia